2013
DOI: 10.1370/afm.1483
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians Provide Feedback On Electronic Health Records In FPM'S User Satisfaction Survey

Abstract: NAPCRG's 2012 Annual Meeting took place in New Orleans, Louisiana the fi rst week of December and was a celebration of NAPCRG's 40th anniversary. The fi rst day's plenary session by T. R. Reid, American author, well-known reporter, documentary fi lmmaker, and commentator on National Public Radio's Morning Edition was both lighthearted and thought-provoking. Reid recounted his experiences obtaining health care in various industrialized nations in which he lived with his family while completing his book, The Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Physicians have experienced highly demanding educational and specialized training and are considered field experts. Findings from prior research suggest that physicians are reluctant to give a positive response to an implementation of an IS (information system) that interferes with their existing routines [32]. A key element in understanding physician use of EHRs is the critical role played by expertise and values in their work processes.…”
Section: Physicians' Work Adaptation Of Ehrmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians have experienced highly demanding educational and specialized training and are considered field experts. Findings from prior research suggest that physicians are reluctant to give a positive response to an implementation of an IS (information system) that interferes with their existing routines [32]. A key element in understanding physician use of EHRs is the critical role played by expertise and values in their work processes.…”
Section: Physicians' Work Adaptation Of Ehrmentioning
confidence: 99%
“…Costs are spiraling out of control, due in part to huge amounts of redundancy and waste [17,18,28]. Research has shown that the healthcare industry is plagued by rapidly increasing costs, poor quality of service, lack of integration of patient care, and lack of information accessible via EHR [14,19,32]. Medical errors arise because of process failures, ineffective communication and lack of information.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been established that physicians have struggled with EHR implementation and the use of the EHR with patient care, resulting in dissatisfaction (Weeks, Keeney, Evans, Moore, and Conrad, 2014;Porter, 2013;Meigs and Solomon, 2016), little is known regarding attitudes of physicians toward electronic portals, with almost no information gathered in the pediatric environment (Keplinger et al, 2013). Since physician perception of and attitude toward the portal plays a crucial role in patient adoption of the portal, it is important to measure these perceptions (Keplinger et al, 2013), and to identify potential concerns or reluctance to adopt the portal within clinical workflow.…”
mentioning
confidence: 99%